Effects of storage time and temperature on hatchability of japanese quail eggs, survival and growth performance of chicks - Mustafa Garip; Süleyman Dere (Eurasian Journal of Veterinary Sciences)
This study was carried out to investigate the effects of storage temperature and periods on quail (Co-turnix coturnix japonica) eggs hatchability and subsequent chick growth performance. Total of 6000 eggs was collected from a quail flock consisting 250 male and 750 female quails of same age, managing and feeding conditions. In the experiment, 3 (storage temperature, 11, 21, 27°C) x 4 (storage period, 1,5, 10, 15 day) factorial design was exerted. The eggs were divided into twelve groups including 12-15 g breeding quality eggs. All eggs were stored in the egg storage room with 75±5% relative humidity. There was not significant effect of egg storage period and temperature on mortality at first ten days and 5 weeks of age and feed conversion ratio throughout the experiment (P>0.05). The average five weeks body weight of quails were obtained lowest in one-day storaged groups (P<0.05). In the temperature groups, the highest body weight was at the 11°C groups (P<0.05). There was a decrease for this trait along with the temperature increase. The lowest body weight was observed in 21 °C group (P<0.05).